Boronia (Rutaceae) is polyphyletic: Reinstating Cyanothamnus and the problems associated with inappropriately defined outgroups. Issue 3 (31st July 2020) - Duretto, Marco F.; Heslewood, Margaret M.; Bayly, Michael J.
Abstract: The monophyly of Boronia (Rutaceae) was tested using 134 accessions of 120 species belonging to 39 genera from subfamily Amyridoideae. Taxa included representatives of all eight sections of Boronia plus species of most genera in the two main clades related to Boronia that had been identified by earlier studies. These samples included a good representation of genera from both rainforest and sclerophyllous biomes. Maximum parsimony and Bayesian inference analyses were performed using three plastid markers ( psbA‐trnH, trnL‐trnF, rbcL ) and two nuclear ribosomal markers (ITS, ETS). Separate analyses of plastid and nuclear sequences using either maximum parsimony or Bayesian inference analyses recovered similar topologies. Apart from Boronia, the broad generic relationships of previous analyses were largely supported. Boronia is polyphyletic with section Cyanothamnus being more closely related to a large clade containing genera found in rainforest, including Melicope, Acronychia and their relatives. The remaining seven sections of Boronia formed a strongly supported and isolated group. Boronia sensu stricto is sister to a clade containing the Cyanothamnus ‐ Melicope ‐ Acronychia clade plus a clade containing Euodia, Zieria and other small genera found in rainforest or sclerophyllous communities. Issues with circumscriptions of ingroups and outgroups for previous analyses of Boronia and the complex relationship between Australasian genera found in rainforest and sclerophyllous communities are both discussed. Cyanothamnus is reinstated at generic level. Appropriate nomenclatural changes are made to transfer all currently recognised series, species, subspecies and varieties of Boronia sect. Cyanothamnus to the genus Cyanothamnus .